Thermo-fluid dynamics of two-phase flow - Ishii, Mamoru (Springer New York, 2011)
Thermo-Fluid Dynamics of Two-Phase Flow, Second Edition focuses on the fundamental physics of two-phase flow. The authors present the detailed theoretical foundation of multi-phase flow thermo-fluid dynamics as they apply to: Nuclear reactor transient and accident analysis; Energy systems; Power generation systems; Chemical reactors and process systems; Space propulsion; Transport processes. This edition features updates on two-phase flow formulation and constitutive equations and new coverage of the lift force and Basset force models, which are of particular significance for those working in the field of computational fluid dynamics, new equations and coverage of detailed one-dimensional drift flux models and a new chapter on porous media formulation, which are important for practicing engineers. Thermo-Fluid Dynamics of Two-Phase Flow, Second Edition is a must have reference for graduate students, scientists and engineers who need in-depth theoretical foundations to solve two-phase flow problems in various technological systems.